Rural Tourism Development: A Case Of Homestays At Tharu Community In Nepal: A CASE OF HOMESTAYS AT THARU COMMUNITY IN NEPAL - Dipak Tharu (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This paper discusses the transformation of indigenous culture and the promotion of rural tourism development towards modernisation from traditional. Rural tourism is a dominant factor in promoting local cultures and heritages along with upgrading local people’s lifestyles. This paper also examines rural tourism development and the existing challenges in Naya Gaon. It explores the potentiality of homestay tourism, which is significantly promoting local people's livelihoods. To better understand the present situation of the village, this study employed mixed methods: qualitative and quantitative. Nevertheless, ethnography as a prior research technique was used for data collection. This technique helped explore the formerly existing local culture, which was transforming into a new model. It also shows that homestay tourism has supported Tharus in the improvement of their socio-economic status and daily habits. In addition, it has enhanced indigenous knowledge and skills to sustain local products. Tharu women have been more empowered both socially and economically. Most noticeably, residents are getting rid of Kamaiyas (Bonded Labourers) and Sukumbashi (Slums).